Colonic polyposis in a 15 year-old boy: Challenges and lessons from a rural resource-poor area. (May 2016) - Kakembo, Nasser; Kisa, Phyllis; Fitzgerald, Tamara; Ozgediz, Doruk; Sekabira, John
Abstract: Introduction: Colorectal polyps usually present with rectal bleeding and are associated with increased risk of colorectal carcinoma. Evaluation and management in resource-poor areas present unique challenges. Presentation of case: This 15 year-old boy presented with 9 years of painless rectal bleeding and 2 years of a prolapsing rectal mass after passing stool. He had 3 nephews with similar symptoms. On clinical assessment and initial exam under anesthesia, an impression of a polyposis syndrome was made and a biopsy taken from the mass that revealed inflammatory polyps with no dysplasia. He was identified during a pediatric surgical outreach to a rural area with no endoscopy, limited surgical services, and no genetic testing available, even at a tertiary center. He subsequently had a three-stage proctocolectomy and ileal pouch anal anastomosis with good outcome after referral to a tertiary care center. The surgical specimen showed many polyps scattered through the colon. Discussion: In the absence of endoscopic surveillance and diagnostic services including advanced pathology and genetic testing, colorectal polyposis syndromes are a significant challenge if encountered in these settings. Reports from similar settings have not included this surgical treatment, often opting for partial colectomy. Nonetheless, good outcomes can be achieved even given these constraints. The case also illustrates the complexity of untreated chronic pediatric surgical disease in rural resource-poor areas with limited health care access. Conclusion: Polyposis syndromes in children present unique challenges in rural resource-poor settings. Good outcomes can be achieved with total proctocolectomy and ileal pouch anastomosis. Highlights: Polyposis syndromes present unique diagnostic and treatment challenges in resource-limited settings. Presentation may be with chronic symptoms and advanced disease. History and physical exam provide valuable information when other imaging and diagnostic modalities are not available. Previous reports from similar settings describe partial colectomies. Total proctocolectomy with ileal pouch reconstruction is feasible and safe.